Sedimentological, geochemical and palaeontological evidence for a neoglacial cold event during the late Holocene in the continental shelf of the northern South Shetland Islands, West Antarctica - Yoo, Kyu-Cheul; Yoon, Ho Il; Kim, Jin-Kyung; Khim, Boo-Keun (Polar Research, 2009)
Two sediment cores obtained from the continental shelf of the northern South Shetland Islands, West Antarctica, consist of: an upper unit of silty mud, bioturbated by a sluggish current, and a lower unit of well-sorted, laminated silty mud, attributed to an intensified Polar Slope Current. Geochemical and accelerator mass spectrometry 14C analyses yielded evidence for a late Holocene increase in sea-ice extent and a decrease in phytoplankton productivity, inferred from a reduction in the total organic carbon content and higher C : N ratios, at approximately 330 years B.P., corresponding to the Little Ice Age. Prior to this, the shelf experienced warmer marine conditions, with greater phytoplankton productivity, inferred from a higher organic carbon content and C : N ratios in the lower unit. The reduced abundance of Weddell Sea ice-edge bloom species (Chaetoceros resting spores, Fragilariopsis curta and Fragilariopsis cylindrus) and stratified cold-water species (Rhizosolenia antennata) in the upper unit was largely caused by the colder climate. During the cold period, the glacial restriction between the Weddell Sea and the shelf of the northern South Shetland Islands apparently hindered the influx of ice-edge bloom species from the Weddell Sea into the core site. The relative increases in the abundance of Actinocyclus actinochilus and Navicula glaciei, indigenous to the coastal zone of the South Shetland Islands, probably reflects a reduction in the dilution of native species, resulting from the diminished influx of the ice-edge species from the Weddell Sea. We also document the recent reduction of sea-ice cover in the study area in response to recent warming along the Antarctic Peninsula.
Keywords: Antarktis; Den lille istid; Vestantarktis; Weddellhavet; diatomeer; fytoplankton; geokjemi; havis; klimaendringer; klimatologi; kontinentalsokkel; marin biologi; mikropaleontologi; oseanografi; sedimenter; sedimentologi; sjøis

The Cosmonaut Sea Wedge - Solli, Kenneth; Kuvaas, Berit; Kristoffersen, Yngve; Leitchenkov, German; Guseva, J; Gandyukhin, V (Marine Geophysical Researches, 2008)
Keywords: Sørishavet; kontinentalmargin; marin geofysikk; sedimenter

Postglacial marine environmental changes in Maxwell Bay, King George Island, West Antarctica - Khim, Boo-Keun; Yoon, Ho Il (Polar Research, 2003)
Sediment textural properties and total organic carbon (TOC) contents of three sediment cores from Maxwell Bay, King George Island, West Antarctica, record changes in Holocene glaciomarine sedimentary environments. The lower sedimentary unit is mostly composed of TOC-poor diamictons, indicating advanced coastal glacier margins and rapid iceberg discharge in proximal glaciomarine settings with limited productivity and meltwater supply. Fine-grained, TOC-rich sediments in the upper lithologic unit suggest more open water and warm conditions, leading to enhanced biological productivity due to increased nutrient-rich meltwater supply into the bay. The relationship between TOC and total sulfur (TS) indicates that the additional sulfur within the sediment has not originated from in situ pyrite formation under the reducing condition, but rather may be attributed to the detrital supply of sand-sized pyrite from the hydrothermal-origin, quartz-pyrite rocks widely distributed in King George Island. The evolution of bottom-water hydrography after deglaciation was recorded in the benthic foraminiferal stable-isotopic composition, corroborated by the TOC and lithologic changes. The Ø18O values indicate that bottom-water in Maxwell Bay was probably mixed gradually with intruding 18O-rich seawater from Bransfield Strait. In addition, the Ø13C values reflect a spatial variability in the carbon isotope distribution in Maxwell Bay, depending on marine productivity as well as terrestrial carbon fluxes by meltwater discharge. The distinct lithologic transition, dated to approximately 8000 yr BP (uncorrected) and characterized by textural and geochemical contrasts, highlights the postglacial environmental change by a major coastal glacier retreat in Maxwell Bay.
Keywords: Sørishavet; geofysikk; geokjemi; marin geologi; miljøendringer; sedimenter

Quantitative models for reconstructing catchment ice-extent using physical-chemical characteristics of lake sediments - Noon, P.E.; Birks, H.J.B.; Jones, V.J.; Ellis-Evans, J.C. (Journal of Paleolimnology, 2001)
The physical characteristics of surface sediments from a suite of pristine lakes on Signy Island, maritime Antarctic, were used to develop a quantitative link between catchment ice-extent and lake-sediment response. Percentage dry weight, median particle size, percentage loss-on-ignition and wet density of the lakes' surface sediments were the most significant variables explaining contemporary catchment ice-extent. Two independent reconstruction models – Partial Least Squares (PLS) and a Modern Analog Technique (MAT) – were applied to dated sediment cores at two sites on Signy Island. The validity of the reconstructions was tested against historical information on catchment ice-extent. With sufficiently high sedimentation rates and sampling resolution, the models can predict sub-decadal changes in ice-extent. The model results are best regarded as indicators of erosion resulting from meltwater activity in the catchment. Comparison of results with Twentieth Century climate records affirms the hypothesis that climatic warming is the most likely cause for the ice retreat observed on Signy Island during the last 40 yrs. Similar reconstruction models using these simple sedimentary measures could be developed for analogous locations in the Antarctic and in Arctic and Alpine regions.
Keywords: Antarktis; innsjø; klimaendringer; paleolimnologi; sedimenter; økologi